User-Created Content: Problems of Genre Formation - M. N. Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article tells about problems of genre formation in social networks. For this goal, the author analyzed a lot of posts, which created users on social networks such as Facebook, Instagram, and VKontakte. In a broad sense, the user content means whole totally information, and in a narrow sense-only those texts which have stable genre features and properties inherent in the genres of journalism. The author remarks that the process of genre formation in social networks is incomplete, and it’s influenced by various factors: technological, creative and communicative. Due to communicative factors, genre forms are dialogical nature. The us- er’s creative activities influenced the appearance of various genre forms in social networks. Technical innovations have influenced the development of visual genres. Photos and videos make the user’s content more attractive and vivid.